2019
DOI: 10.1177/0145561319849947
|View full text |Cite
|
Sign up to set email alerts
|

Modified Infrahyoid Myocutaneous Flap for Laryngopharyngeal Reconstruction

Abstract: The laryngopharyngeal reconstruction in patients with pyriform sinus carcinoma continues to be a challenge for surgeons. In this article, we describe our experience with laryngopharyngeal reconstruction in patients with pyriform sinus carcinoma using the modified infrahyoid myocutaneous flap (IHMCF). The modified incision design for the modified IHMCF and clinical outcomes are also detailed here. Between January 2012 and February 2018, 10 patients with hypopharyngeal squamous cell carcinoma who underwent laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…15,16 Neither is any microsurgical expertise or instruments nor a second team to harvest the flap required, also it is a one-step procedure all of these contributing drastically to cutting down the cost of surgery. 13,14 Deganello et al, in their study have also shown great economic benefits with neck flaps when compared to free flaps. 18 The mean discharge time in our study was just seven days post-surgery.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…15,16 Neither is any microsurgical expertise or instruments nor a second team to harvest the flap required, also it is a one-step procedure all of these contributing drastically to cutting down the cost of surgery. 13,14 Deganello et al, in their study have also shown great economic benefits with neck flaps when compared to free flaps. 18 The mean discharge time in our study was just seven days post-surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Since the infrahyoid flap was close to the recipient site there are no additional scars on the neck. 11, 12, 14, 15 It was well accepted by the patients since the donor site was also in the vicinity of the recipient site. 13, 16 The distress and recovery at the infrahyoid donor site were quite negligible when compared to free flaps as they can be closed by primary intention with Z-plasty as and when required.…”
Section: Discussionmentioning
confidence: 99%
“…(1,3,4) However, like other regional flaps and free flaps, there are concerns such as partial or incomplete flap failure and subsequent flap necrosis, about this flap as well as excessive flap volume hypotrophy. (5)(6)(7)(8) On the other hand, the most important limitation of the infrahyoid flap is its low bulk, which makes it not suitable for more advanced tumors that are accompanied by simultaneous resection of more than 50% of the anterior tongue and nearly 50% of the base of the tongue. The small size of this flap leads to swallowing and Speech problems and aspiration are used in the reconstruction of extensive tounge defects.…”
Section: Introductionmentioning
confidence: 99%